Selección de hábitat y comportamiento sexual de Sulcophanaeus velutinus (Murray 1856) (Coleoptera: Scarabaeidae: Scarabaeinae) en un bosque de montaña en Colombia - Escobar, Federico (Instituto de Ecología, A.C., 2022)
Information about habitat preferences, activity and sexual behavior of Sulcophanaeus velutinus (Murray 1826), a common species of Neotropical mountains are presented.